Analisis Penggunaan Media Pembelajaran Kreatif dalam Pembelajaran Matematika Sekolah Dasar Kelas 1 - Chiara Meliani; Syifa Qonita Khairunnisa; Kowiyah Kowiyah (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to analyze the comparison of using contextual learning media (concrete) involving technology in improving the mathematics learning outcomes of first-grade elementary school students. The research method used is a qualitative method with a descriptive approach. Data collection was conducted through observation, interviews, and documentation to understand students' interactions with creative learning media and its impact on their understanding of basic mathematical concepts. The results of this study indicate that the use of learning media, both contextual (concrete) and involving technology, such as visual aids and educational games, can increase students' interest in learning, help them understand the material more easily, and have a positive impact on their mathematics learning outcomes. It is hoped that the use of innovative and creative learning media can continue to be applied in mathematics education to support the cognitive development and interest of students in mathematics from an early age. However, the use of concrete learning media involving counting boards and jumping frogs is hindered by time efficiency.